Ultrafast spin-flip exciton conversion and narrowband sky-blue luminescence in a fused polycyclic selenaborin emitter - Keshri, Sudhir K.; Liu, Guanting; Yasuda, Takuma (Frontiers in Chemistry, 2024)
Thermally activated delayed fluorescence (TADF) materials with high photoluminescence quantum yields and fast reverse intersystem crossing (RISC) capabilities are highly desirable for applications in high-efficiency organic light-emitting diodes. Herein, we report the synthesis as well as structural and photophysical properties of 5,9-diselena-13b-boranaphtho[3,2,1-de]anthracene (SeBSe) as a narrowband-emissive TADF material. The incorporation of two selenium atoms into the boron-fused pentacyclic π-core results in a small singlet-triplet energy gap (ΔEST) and thereby significant TADF properties. Moreover, theoretical calculations revealed a noticeable spin-orbit coupling enhancement between the singlet and triplet manifolds in SeBSe by virtue of the heavy-atom effect of selenium atoms. Consequently, SeBSe allows ultrafast spin-flip RISC with the rate constant surpassing 10 8 s -1 , which far exceeds the corresponding fluorescence radiative decay rate (~10 6 s -1 ), enabling an ideal singlet-triplet superimposed excited state.